Comparison of efficacy and safety between two different irbesartan, generic vs branded, in the treatment of Korean patients with mild-to-moderate hypertension: an 8-week, multicenter, randomized, open-label, Phase IV clinical study - Han SH; Oh GC; Kwon HM; Park CG; Kim IJ; Hwang GS; Yoo BS; Park SH; Lee KJ; Kim HS (Dove Medical Press, 2018)
Seung Hwan Han,1 Gyu Chul Oh,2 Hyuck Moon Kwon,3 Chang Gyu Park,4 In Jai Kim,5 Gyo-Seung Hwang,6 Byung Su Yoo,7 Seong Hoon Park,8 Kwang Je Lee,9 Hyo-soo Kim21Division of Cardiology, Department of Internal Medicine, Gachon University College of Medicine, Gil Hospital, Incheon, Republic of Korea; 2Division of Cardiology, Department of Internal Medicine, Seoul National University College of Medicine, Seoul, Republic of Korea; 3Cardiology Division, Department of Internal Medicine, Gangnam Severance Hospital, Yonsei University College of Medicine, Seoul, Republic of Korea; 4Division of Cardiology, Cardiovascular Center, Korea University Guro Hospital, Seoul, Republic of Korea; 5Department of Cardiology, CHA Bundang Medical Center, CHA University, Seongnam, Republic of Korea; 6Department of Cardiology, Ajou University School of Medicine, Suwon, Republic of Korea; 7Division of Cardiology, Department of Internal Medicine, Wonju Severance Christian Hospital, Wonju, Republic of Korea; 8Division of Cardiology, Department of Internal Medicine, Ewha Womans University College of Medicine, Seoul, Republic of Korea; 9Division of Cardiology, Department of Internal Medicine, Chung-Ang University Hospital, Seoul, Republic of Korea Purpose: This study aimed to compare the efficacy and safety of generic and branded irbesartan for 8 weeks in patients with mild-to-moderate essential hypertension.Patients and methods: We screened 221 patients with mild-to-moderate hypertension. After exclusion per study criteria, 177 subjects were randomized to receive 150 mg generic irbesartan (n=91) or branded irbesartan (n=86) as the intention to treat set. The primary efficacy endpoint of this study was the change in mean sitting diastolic blood pressure (SiDBP) from baseline to 8 weeks between the generic and branded irbesartan groups. The secondary efficacy endpoints were the change in mean SiDBP at Week 4 from baseline and the change in mean sitting systolic blood pressure (SiSBP) at Weeks 4 and 8 from baseline in both groups. All safety issues were evaluated.Results: At Week 8, the generic and branded irbesartan groups showed significantly reduced SiDBP (−10.3±8.0, −10.7±7.7 mmHg, all P<0.0001) compared with baseline values, and the mean between-group difference in SiDBP change after 8 weeks of treatment was −0.4±1.2 mmHg, showing the non-inferiority of generic irbesartan vs branded irbesartan. Furthermore, secondary efficacy, which was the mean change of SiDBP from baseline at 4 weeks, was comparable between the two groups (−9.4±8.1 vs −9.9±7.4 mmHg, P=0.69). There were no between-group differences in mean changes of SiSBP after 4 or 8 weeks of treatment (P=0.78, P=0.97, respectively), or in the incidence of adverse effects (16.7 vs 24.4%, P=0.20).Conclusion: Generic irbesartan treatment in patients with mild-to-moderate essential hypertension has shown effective antihypertensive effects comparable with the branded irbesartan treatment, with similar incidence of adverse effects.Keywords: irbesartan, generic medicine, hypertension, anti-hypertensive